High-frequency, high-intensity electromagnetic field effects on Saccharomyces cerevisiae conversion yields and growth rates in a reverberant environment. (July 2018) - Bertrand, Emmanuel; Pasquier, Christophe; Duchez, David; Girard, Sebastien; Pons, Agnès; Bonnet, Pierre; Creuly, Catherine; Dussap, Claude-Gilles
Highlights: Rational method to assess intensity and specific absorption rate in submerged cultures. Average mean electric field is respectively 6.11 and 3.44 V.m −1 at 900 and 2400 MHz. Culture dielectric properties limit exposition to the electromagnetic field. No effect on growth rate and ethanol yield noticed. Possible effect on glycerol and acetate yields to be further investigated. Abstract: Studies of the effects of electromagnetic waves on Saccharomyces cerevisiae emphasize the need to develop instrumented experimental systems ensuring a characterization of the exposition level to enable unambiguous assessment of their potential effects on living organisms. A bioreactor constituted with two separate compartments has been designed. The main element (75% of total volume) supporting all measurement and control systems (temperature, pH, agitation, and aeration) is placed outside the exposure room whereas the secondary element is exposed to irradiation. Measurements of the medium dielectric properties allow the determination of the electromagnetic field at any point inside the irradiated part of the reactor and are consistent with numerical simulations. In these conditions, the growth rate of Saccharomyces cerevisiae and the ethanol yield in aerobic conditions are not significantly modified when submitted to an electromagnetic field of 900 and 2400 MHz with an average exposition of 6.11 V.m −1 and 3.44 V.m −1 respectively.